2021
DOI: 10.2174/1381612827666210222114441
|View full text |Cite
|
Sign up to set email alerts
|

Statistically Designed Extraction of Herbs Using Ultrasound Waves: A Review

Abstract: Background: Extraction is the foremost step to isolate the natural constituents from a medicinal plant and leads the process of development of herbal formulation from bench to bed. Introduction: In the field of extraction, the optimization approach helps in achieving better yield and quality where a response of concern is determined or influenced by various variables. This review aimed at congregating the application of different statistical designs (CCD/BBD) to optimize the Ultrasound assisted extraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…All of these factors enhance the disruption of cell walls, enhancing the contact of extractible compounds with the solvent and their partition in the extraction environment [14] . It was also shown that the UAE could be more effective when the influence of each extraction parameter is well defined and correlated with the properties of the extracted matrix, these features being overall reflected by the final quality of the obtained extracts in terms of their bioactive potential [12] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…All of these factors enhance the disruption of cell walls, enhancing the contact of extractible compounds with the solvent and their partition in the extraction environment [14] . It was also shown that the UAE could be more effective when the influence of each extraction parameter is well defined and correlated with the properties of the extracted matrix, these features being overall reflected by the final quality of the obtained extracts in terms of their bioactive potential [12] , [15] , [16] .…”
Section: Introductionmentioning
confidence: 99%
“…The various parameters such as solvent/solid ratio, sonication time, ultrasonic power, amplitude, and temperature affect the extraction efficiency in UAE and need to be optimized for improved yield ( 57 , 58 ). Based on the literature study and results of our previously published paper, we can say that the UAE is successful at lower temperature (40–70°C) and low sonication frequency (20–30 KHz) ( 3 , 59 ). Therefore, for this study, the experiments were carried out at 24 KHz and at 70°C.…”
Section: Resultsmentioning
confidence: 87%
“…These days, UAE is effectively employed for the extraction of herbs owing to its improved and better results with a green approach. The acoustic cavitation effect produced by the ultrasound waves in the drug particles is mainly responsible for the upgraded diffusion of menstruum and results in improved EY ( 3 ). UAE is considered to be the green technique that can provide high reproducibility in small time and low energy inputs ( 52 56 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations